Pengaruh Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Karyawan Divisi Teleoperation PT. keuangan BFI Indonesia, Tbk BSD Serpong - Khasanah, Nisfatun; Amelia, Rizka Wahyuni (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of Leadership (X1) and Work Motivation (X2) on Employee Performance (Y) in the Teleoperation Division at PT. BFI Finance Indonesia, Tbk. BSD Serpong. The method used is a quantitative method. The data sources for this research are in the form of questionnaires, data, observations and literature studies. The data methods used in this research are validity tests, reliability tests, classical assumption tests, correlation coefficients, linear regression tests and significant tests including the T and F statistical tests. Using SPSS version 26 software. The results of this research show that leadership has a significant effect on employee performance with the regression equation Y = 5.310 + 0.749X1, a correlation value of 0.815, meaning the two variables have a strong level of relationship. The coefficient of determination value was 64.4 and the hypothesis test obtained tcount 11.430 > ttable 1.996. Motivation has a significant effect on employee performance with the regression equation Y = 1.219 + 0.995X2, a correlation value of 0.897, meaning that the two variables have a strong level of relationship. The coefficient of determination value was 80.4%, and the hypothesis test obtained tcount 16.472 > ttable 1.996. Leadership and motivation simultaneously have a significant effect on employee performance with a regression equation of 16.721+0.258X1+ 0.297X2+e. A correlation value of 0.897 means that the independent variable and the dependent variable have a very strong level of relationship. The coefficient of determination value is 80.5% while the remaining 19.5% is influenced by other factors. Hypothesis testing obtained an F-count value of 134.075 > F-table 2.764.